HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DAN KOORDINASI MATA-TANGAN TERHADAP SERVIS ATAS KLUB BOLA VOLI PUTRI SMK N 2 TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Saputra, Fiki; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: To find out the Correlation between Arm and Shoulder Muscle Explosive Power and Eyes-Hands Coordination On Upper Service SMK N 2 Teluk Kuantan Female Volleyball Club. This type of research is correlation research, the population of this research is SMK N 2 TelukKuantan Female Volleyball Club, the sample of this research is SMK N 2 TelukKuantan Female Volleyball Club which is 25 in amount. From the first calculating analysis the correlation between X1 and Y, which rtable on significant level α (0,05) = 0,404 means rresult(0,424) > rtable(0,404), means hypothesis is accepted and there is a very strong correlation between Arm and Shoulder Muscle Explosive Power and Eyes-Hands Coordination On Upper Service SMK N 2 TelukKuantan Female Volleyball Club, the second analysis between Eyes-Hands Coordination (X2) on Upper Service SMK N 2 TelukKuantan Female Volleyball Club (Y), which rtable on significant level α (0,05) = 0,404 means rresult(0,248) < rtable(0,404), means hypothesis is rejected and there is a weak correlation between Eyes-Hands Coordination on Upper Service SMK N 2 Teluk Kuantan Female Volleyball Club, the third analysis, the correlation of Arm and Shoulder Muscle Explosive (X1), and Eyes-Hands Coordination (X2) on Upper Service (Y) is obtained, where rtab on significant level α (0,05) = 0,404, means Rresult(0,526) > rtable(0,404). It can be concluded that the correlation between (X1) and (X2) on Y or The Correlation between Arm and Shoulder Muscle Explosive Power and Eyes-Hands Coordination On Upper Service SMK N 2 Teluk Kuantan Female Volleyball Club is strong. Therefore Upper Service SMK N 2 Teluk Kuantan Female Volleyball Club can be predicted by coordination and power.Key Words: Explosive, Coordination, and Upper Service